Pembuatan Mural Di Kantor Kelurahan Dengan Tema Lingkungan Hidup - Azalia Fajri Yasin; Muhammad Mardan Syamsi; Desy Puspita Ningrum (CV. Multi Kreasi Media, 2024)
This article discusses the creation of environmental - themed murals at the Klawalu Village Office in Sorong City. Through collaboration between students and the local community, this project aims to raise environment awareness and highlight important issues such as waste, the ocean, and forests. Using mural art as a medium, the student succesfully depicted the environmental realities faced by Sorong City and inspired the younger generation to take action for environmental sustainibility. This mural project demonstrates that collaboration between higher education and the community can result in significant positive chages for our environment.